Youth cyberslang in communication - Makulbayeva, А.А.; Baidrakhmanov, Д.Х.; Ibrayeva, Ж.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article presents the results of studying the corpus of cyberslang units used among young people. It forms an understanding of the concept of "cyberslang", shows its influence on the Kazakh language among the young generation, and its importance in developing scientific achievements. Moreover, the article analyzes the similarities and differences within the meanings of cyberslang units. The relevance of the article relies on constant changes at all levels of linguistic communication, especially in the era of global information exchange and the constant development of technologies. Special attention is devoted to the issue of language purity or "language ecology". The analysis of literature by Kazakhstani and foreign authors is revealed. It also studies approaches to language ecology. The author touches upon the issues of "language economy" as one of the reasons for the emergence of Internet slang within youth communication to save time, as well as to disguise the meaning of a message from strangers in chats and social networks. The main objective of the article is to analyze the sources of cyberslang in the media space and use the method of comparative analysis to identify the linguistic and functional features of cyberslang.